A meta-analysis: single or double dartos flap layer in tubularized incised plate urethroplasty to prevent urethrocutaneous fistula? - Yuan, Yi; Wang, Yu-wen; Liang, Yan-nei; Wang, Yu-ying; Ho, Jun-jie; Peng, Tong-yu; Zhao, Zhang; Deng, Nan (Frontiers in Pediatrics, 2023)
Backgrounds Urethrocutaneous fistula is one of the most common complications after urethroplasty. This meta-analysis aims to evaluate the superiority of double flap to single flap in preventing fistula during tubularized incised plate urethroplasty (TIPU), one of the most frequently used operations for hypospadias. Methods We extracted clinical trials under included criteria : (1) children with TIPU, (2) a comparison of single and double flap layer, (3) record of complications, with excluded cirteria: (1) non-comparion, (2) lack of data. Finally, 13 studies from Pubmed, Cochrane Library, Scopus, and Embase, have been investigated, with 1185 patients in total from 2005 to 2022. The quality assessment was conducted according to the Cochrane handbook and Newcastle-Ottawa Scale. A mixed-effect model was utilized to weigh the risk of fistula, phallic rotation, meatal stenosis, and wound dehiscence by the software Review manager V.5.4. Results The double dartos flap layer group (DDF) excels in descending the risk of postoperative fistula [OR = 9.56; 95% CI (4.76, 19.22); P < 0.00001] and phallic rotation [OR=31.26; 95%CI (9.60, 101.84); P<0.00001], while there are no differences in the rate of meatal stenosis [OR=1.49; 95%CI (0.73, 2.70); P=0.31] and wound dehiscence [OR = 2.30; 95% CI (0.80, 6.63); P=0.12]. Conclusions The routine utility of a double dartos flap layer is recommended as a potential treatment during the tubularized incised plate urethroplasty.